嗜睡症、换脸政策，空虚感 ：论韩丽珠《空脸》的 病态书写 = Narcolepsy, face change policy, emptiness : pathological writing in Hon Lai Chu Kong Lian - 蔡丽莲 Chua, Li Lian (Nanyang Technological University, 2020)
韩丽珠是香港新生代独具风格的作家，拥有“香港卡夫卡”之称。目前学术界对她的研究甚少，多数学者以异化、身体书写、精神分析，影响研究来探讨作品。他们注意到作者对病态书写的偏爱，但未深究。因此，本文以病态书写为切入点来研究小说《空脸》，希望能拓展新题材与视角。 本文以三个议题展开论述：嗜睡症、换脸政策，空虚感。首先，本文将探讨嗜睡症，以分析责任感与疲劳、失败的沟通，商业化的社会，来体现出人民在社会中麻木中生存。其次，本文将探讨换脸政策，分析逃逸的途径、辩解的空洞，面具的保护，来体现出人民在身份与工具之间生存的现象。再次，本文将探讨空虚感，以自我分裂、疏远的相处，屠脸的创伤，来体现出人民精神萎靡中审视的现象。 笔者发掘，韩丽珠书写病态的动机是要揭露社会的堕落，以此去批判社会制度压榨、操控，摄取人民的身心灵，呈现出作者的焦虑与岌岌可危的现实意义。 Hon Lai Chu is one of the new generation author in Hong Kong with a unique style of writing, mostly known as “Hong Kong Kafka”. Currently, there is little research on her novels. Most scholars used alienation, body writing, psychoanalysis and influence studies to explore her works. They noticed the author’s preference for pathological writing but did not delve into it. Therefore, this graduation thesis uses pathological writing as the key concept to study the novel Kong Lian, so as to explore new topics and perspectives. This graduation thesis discusses on three topics: Narcolepsy, Face-Changing Policy, Emptiness. Firstly, this article explores narcolepsy. It analysis the relation between responsibility and fatigue, followed by the failure in communication within relationship, commercialize society, so as to prove the numbness of the society. Secondly, this article explores face-changing policy. It analysis as a means of escape and justification, and brings up the importance of wearing a face mask, so as to reflect the phenomenon of survival between identity and tools. Thirdly, this article will explore the sense of emptiness. It analysis self and ego, followed by the alienation in a relationship, and discuss “Slaughter Face” incident, so as to prove peoples’ weak mental state. Hon Lai Chu uses pathological writing to expose the degeneration of society, so as to criticize the oppression and manipulation of society system. This further shows the author’s anxiety and society practical significance.